Using Encryption Square Keywith One-Dimensional Matrix for Enhancing RGB Color Image Encryption-Decryption - Mohammad Rasmi AL-Mousa; Fadi Al-salameen; Khaled Eisa Alqawasmi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recently, the security of digital images becomes an important issue with the rapid growth of digital communication and multimedia application. Recent cryptography algorithms are providing essential techniques to protect information and multimedia data. However, those algorithms are usually suffering from the problem of time-consuming. Encryption algorithms have been growth quickly and many image encryption methods have been used to protect information and multimedia data from unauthorized access. This research presents effective technique for image encryption which employs Red, Green and Blue (RGB) components of the RGB color image. The proposed technique utilizes matrix multiplication and inverse matrices for encryption-decryption purpose. Moreover, the effectiveness of the proposed encryption-decryption techniques lay on minimizing the encryption-decryption time and the square error between the original and the decrypted image.  The evaluations of the proposed technique were done using many images with different sizes, while the ex perimental results show that the improved encryption technique time are greatly reduced compared with “RGB Color Image Encryption-Decryption Using Gray Image” method.  The proposed technique has a high confidentiality level through using confusion diffusion sequentially with a square matrix key and two vectors keys. However, those keys are generated randomly and make the process of hacking the image very difficult.